Use of chatbots based on artificial intelligence for higher education - Martinez Zambrano, Hilary Rosmery (2024)
Education has been evolving until today, allowing the use of technology and the diversity of digital tools to be incorporated into the training process of higher education students. That is why the use of AI-based Chatbots in higher education is a growing trend that has been transforming the learning experience, as they help to solve some of the current challenges faced in this sector. Therefore, we set out to evaluate the factors that affect the adoption of the use of AI-based Chatbot to improve the quality of student learning in higher education That is why, in this research, we used the quantitative method by collecting data, for which inclusion and exclusion criteria were applied, 19 articles were selected from the IEEE and Scopus databases. The results showed that AI-based Chatbots offer personalization, instant interaction, and fast and automated support to higher education students, as they can provide answers to frequently asked questions, guide students through available resources, assist in problem solving, and offer reminders of assignments and deadlines. It was concluded that the outcome of the research will help Chatbot developers, higher education institutions and higher education providers to better understand the needs of students and at the same time provide them with an interactive learning and communication platform.